Survival Outcomes of Patients With Breast Cancer Diagnosed Using Vacuum-Assisted Biopsy: A Nationwide Study From the Korean Breast Cancer Society - Kim, Bong Kyun; Ahn, Sung Gwe; Oh, Se Jeong; Kim, Hakyoung; Kang, Eunyoung; Jung, Yongsik; Do Byun, Kyung; Lee, Jina; Sun, Woo Young (Journal of breast cancer, 2022)
Breast cancer is mainly diagnosed using core needle biopsy (CNB), although other biopsy methods, including vacuum-assisted biopsy (VAB), may also be used. We compared differences in clinical characteristics and prognoses of patients with breast cancer according to biopsy methods used for diagnosis. A total of 98,457 patients who underwent various biopsy methods (CNB, fine-needle aspiration [FNA], VAB, and excisional biopsy) for diagnosing breast cancer were recruited. Using CNB as a reference, related clinicopathological factors and prognostic differences between biopsy methods were analyzed retrospectively using large-scale data from the Korean Breast Cancer Society Registration System. The associations between biopsy methods and clinicopathological factors were compared using multinomial logistic regression analysis, and the prognoses of patients undergoing the different biopsy methods, as breast cancer-specific survival (BCSS) and overall survival (OS), were compared using the Kaplan-Meier method and Cox proportional hazard model. Univariate and multivariate analyses showed that unlike FNA, both VAB and excisional biopsy were significantly associated with tumor size, palpability, tumor stage, and histologic grade as relatively good prognostic factors compared to CNB. In particular, VAB showed lower odds ratios for these factors than excisional biopsy. In the univariate analysis, the prognosis of patients undergoing VAB was better than that of those undergoing CNB with respect to BCSS (hazard ratio [HR], 0.188, < 0.001) and OS (HR, 0.359; < 0.001). However, in the multivariate analysis, there were no significant prognostic differences from CNB in both BCSS and OS; differences were only evident for FNA. In this study, we showed that the characteristics of breast cancer differed according to various biopsy methods. Although VAB is not a standard method for breast cancer diagnosis, it showed no prognostic differences to CNB.